Recent Advances in Gastroretentive Drug Delivery Systems: A Review - Kumar, Kiran (Asian Journal of Pharmaceutics (AJP), 2022)
Many advances have been achieved in the study and development of oral drug delivery system in recent years. The conception of novel drug delivery system originated to address a specific issue linked to the physicochemical characteristics of drug molecules and associated formulations. The goal of this study is to synthesize new research on gastroretentive drug delivery systems to provide an update on pharmacological techniques employed in improving gastric residence time. Gastroretentive floating drug delivery systems, swelling and expanding systems, polymeric bioadhesive systems, modified-form systems, high density systems, and other delayed gastric emptying devices are now employed. These technologies are quite useful in resolving various issues that arise during the development of various dosage forms. Because of the short residence period, oral absorption of medicines with a limited absorption of drugs inside the upper intestinal wall results in low bioavailability with traditional dose forms. Controlled drug delivery systems with an extended residence period in the stomach can be employed to circumvent this constraint and boost the bioavailability of these medications. A gastric retention drug delivery device can be used to extend medication residence period in the upper gastrointestinal tract. This review article focuses on the most recent advances in expandable technological advancement in floating drug delivery systems, with a particular emphasis on the primary mechanism of floatation and the benefits of achieving gastric retention, as well as a brief collection of various polymers used in floating drug delivery systems.